Phenotypic Characterization of Postharvest Fruit Qualities in Astringent and Non-astringent Persimmon (Diospyros kaki) Cultivars - Yadav, Akhilesh; Fennec, Anton; Guan, Changfei; Yang, Yong; Kochanek, Bettina; Israel, David; Izhaki, Anat; Zilkah, Shmuel; Friedman, Haya (Frontiers in Genetics, 2021)
Phenotypic characterization of postharvest traits is essential for the breeding of high-quality fruits. To compare postharvest traits of different genetic lines, it is essential to use a reference point during fruit development that will be common to all the lines. In this study, we employed a non-destructive parameter of chlorophyll levels to establish a similar physiological age and compared several postharvest traits of ten astringent and seven non-astringent persimmon cultivars. The fruit's traits examined were astringency, weight, total soluble solids (TSS), titratable acidity (TA), chlorophyll levels (IAD), color (hue), firmness, color development and firmness loss during storage, crack development, and susceptibility to Alternaria infection. Although the chlorophyll (IAD) index and color (hue) showed a high correlation among mature fruits of all cultivars, the chlorophyll parameter could detect higher variability in each cultivar, suggesting that IAD is a more rigorous parameter for detecting the developmental stage. The average weight, TSS, and TA were similar between astringent and non-astringent cultivars. Cracks appeared only on a few cultivars at harvest. Resistance to Alternaria infection and firmness were lower in astringent than in non-astringent cultivars. Only the astringent cultivar ‘32’ was resistant to infection possibly due to the existence of an efficient peel barrier. It was concluded that a high correlation existed between astringency, susceptibility to Alternaria infection, and firmness. Cracks did not correlate with astringency or firmness. The phenotypic traits evaluated in this work can be used in future breeding programs for elite persimmon fruits.